Impact of a slaughterhouse hygiene intervention in western Kenya - Ambler, Kate; Cook, Elizabeth A.J.; Hoffmann, Vivian; Kiarie, Alice; Otoigo, Lilian; Wagner, Julia (International Food Policy Research Institute, 2024)
Adherence to strict hygiene standards in slaughterhouses is critical for ensuring food safety and protecting workers from zoonotic disease. The International Livestock Research Institute (ILRI) and International Food Policy Research Institute (IFPRI) conducted a study to evaluate the impact of low-cost interventions on hygiene practices in slaughterhouses in western Kenya.